Proteomics Approaches to Identify Mono(ADP-ribosyl)ated and Poly(ADP-ribosyl)ated proteins - Vivelo, Christina A. (Proteomics, 2014)
ADP-ribosylation refers to the addition of one or more ADP-ribose units onto protein substrates and this protein modification has been implicated in various cellular processes including DNA damage repair, RNA metabolism, transcription and cell cycle regulation. This review focuses on a compilation of large-scale proteomics studies that identify ADP-ribosylated proteins and their associated proteins by mass spectrometry using a variety of enrichment strategies. Some methods, such as the use of a poly(ADP-ribose)-specific antibody and boronate affinity chromatography and NAD(+) analogues, have been employed for decades while others, such as the use of protein microarrays and recombinant proteins that bind ADP-ribose moieties (such as macrodomains), have only recently been developed. The advantages and disadvantages of each method and whether these methods are specific for identifying mono(ADP-ribosyl)ated and poly(ADP-ribosyl)ated proteins will be discussed. Lastly, since poly(ADP-ribose) is heterogeneous in length, it has been difficult to attain a mass signature associated with the modification sites. Several strategies on how to reduce polymer chain length heterogeneity for site identification will be reviewed.